2014
DOI: 10.1177/1933719114522518
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of HeLa Cell Contamination in HES Cells: Call for Cell Line Authentication in Reproductive Biology Research

Abstract: Continuous cell lines are used frequently in reproductive biology research to study problems in early pregnancy events and parturition. It has been recognized for 50 years that many mammalian cell lines contain inter-or intraspecies contaminations with other cells. However, most investigators do not routinely test their culture systems for cross-contamination. The most frequent contributor to cross-contamination of cell lines is the HeLa cell isolated from an aggressive cervical adenocarcinoma. We report on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…In addition to their use as research tools, false or misidentified cell lines such as HL-7702, TSCCA and BEL-7402 have been used in anti-cancer drug screening programs in respected centers in China. WISH, which has been reported as a HeLa contaminant for decades [37], was also on the panel of cell models for differentiation [38] in these institutions under its false identity-amnion cell line of human origin. Despite sporadic reports about cell line cross-contamination provided by cell repositories in China through systematic quality control check of their own cell lines, the tainted cell lines are still on sale for use.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their use as research tools, false or misidentified cell lines such as HL-7702, TSCCA and BEL-7402 have been used in anti-cancer drug screening programs in respected centers in China. WISH, which has been reported as a HeLa contaminant for decades [37], was also on the panel of cell models for differentiation [38] in these institutions under its false identity-amnion cell line of human origin. Despite sporadic reports about cell line cross-contamination provided by cell repositories in China through systematic quality control check of their own cell lines, the tainted cell lines are still on sale for use.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that soluble LDLR (sLDLR) secretion by cells can be induced by type I IFN and that sLDLR can inhibit VSV infection in WISH cells (this cell line was recently shown to be misidentified and identical to HeLa cells) (51)(52)(53). Although this mechanism cannot be responsible for the inefficient attachment of VSV to HPAF-II cells in our monolayer and suspension attachment assays (cells were washed before incubation with VSV), this sLDLR-mediated inhibition of VSV attachment could happen during multistep infection of cells, where HPAF-II cells show very strong resistance to VSV infection and replication.…”
Section: Vsv Attachment To Hpaf-ii Cells Is Impairedmentioning
confidence: 99%
“…First, to test whether sLDLR can inhibit VSV infectivity in PDAC cells, sLDLR and VSV or VSV alone was added to the cells, and the cells were incubated for 30 min at 37°C (the assay was conducted as described previously [51][52][53]). Cells were then washed to remove any unbound virus and overlaid with agar to prevent secondary infections.…”
Section: Vsv Attachment To Hpaf-ii Cells Is Impairedmentioning
confidence: 99%
“…Among these 70 misidentified human cell lines, 41 cell lines were used worldwide and 29 cell lines were established by Chinese scholars. 15 cell lines were in the Database of Cross-Contaminated or Misidentified Cell Lines of ICLAC (International Cell Line Authentication Committee), including the notable HeLa-replaced cell lines (ACC-2, ACC-M, KB and HEP-2) 8 11 , the glioma cell line SF767, which was substituted with the human cervical cancer cell line ME-180, and the nasopharyngeal carcinoma tumor lines CNE-1 and CNE-2, which are thought to be fusion cell lines between HeLa and another, unknown cell line 12 , 13 . Another 14 misidentified cell lines were reported in some papers 5 , 14 , 15 .…”
Section: Resultsmentioning
confidence: 99%
“…It was once the most widely used cell line due to its hardiness and rapid growth rate. However, it has been demonstrated that HeLa cells have contaminated many other cell lines; they have overgrown and completely replaced such original cell lines as WISH, KB, Hep-2, Chang Liver, INT407 and the adenoid cystic carcinoma cell lines ACC-2, ACC-3 and ACC-M 5 , 8 11 . From 1969 to 2004, 220 publications in the PubMed database were found to have used HeLa-contaminated cell lines 42 .…”
Section: Discussionmentioning
confidence: 99%